Evaluation of wound healing properties of Clinicanthus nutans (Burm.F.) Lindau (Belalai gajah) and its related biochemical activities on male Sprague-Dawley rats - Ramasamy, Sathiavani (2021)
Clinacanthus nutans Lindau (C. nutans), also known as Sabah Snake Grass, of the Acanthaceae family has been widely used in traditional medicine and scientific investigations of this plant have shown multitude therapeutic benefits ranging from anticancer, antioxidant, antidiabetic, antimicrobial, immunomodulatory, anti-inflammatory and analgesic activities. C. nutans has also shown promising properties in preliminary wound healing rat models by the integrity of epidermal tissue at the lesion sites. The objective of this study is to determine the most potent solvent extracts of C. nutans to develop a topical herbal cream that will be efficacious on the wound lesions in Sprague Dawley rat models along the lines of biochemical and histological assessments. The plant leaves were subjected to hot solvent extraction and crude extracts were derived from ethanol, methanol, chloroform and water. The extracts were subjected to both phytochemicals assessments which comprised of phenols, flavonoids and tannins and antioxidant activity assessments by (2,2-diphenyl- 1-picrylhydrazyl) DPPH and (Azino-bis-3-ethylbanzthiazoline-6-sulphonic acid) ABTS assays prior to conducting the in vivo excision wound experiment in rat models. Methanol extract demonstrated the highest phenolic, flavonoid and tannin content of (12.96 ± 1.91 mg GAE/gm), (10.06 ± 1.68 mg QUE/gm) and (7.15 ± 0.64 mg TAE/gm). It was found that, methanol extract could scavenge DPPH with the maximum scavenging activity of 56.37 ± 0.70% and with an IC50 of 222.69 ± 0.29 μg/ml and for ABTS, aqueous extract showed highest scavenging activity of 57.50 ± 0.52% with an IC50 of 149.45 ± 0.24 μg/ml respectively. The rats were arranged into 6 groups, each group consist of 6 rats except the negative control group which consist of 3 rats. Group 1 (control), group 2 (standard / Dettol antiseptic cream), group 3 was aqueous extract of C. nutans with dose 1 (12.5 mg/ml of aqueous extract of C. nutans), dose 2 (25.0 mg/ml of aqueous extract of C. nutans) and dose 3 (50.0 mg/ml of aqueous extract of C. nutans). Group 4 was methanolic extract of C. nutans with dose 1 (12.5 mg/ml methanolic extract of C. nutans), dose 2 (25.0 mg/ml methanolic extract of C. nutans) and dose 3 (50.0 mg/ml methanolic extract of C. nutans) group 5 (cream base), group 6 (herbal cream). The most effective dosages were 12.5 mg/ml of methanol extract and 50.0 mg/ml of aqueous extract, combined and produced a topical herbal cream which was tested in vivo using rat models again. Subsequently, the mechanism of action of the C. nutans topical herbal cream was assessed using biochemical parameters like hydroxyproline, collagen and hexosamine and histopathological changes. Topical herbal cream by incorporating methanol extract 12.5 mg/ml and aqueous extract 50.0 mg/ml showed a significant wound repair and skin regeneration about (99.5 ± 0.22%) wound contraction at Day 15 compared to control groups. Biochemical parameters like hydroxyproline (64.11 ± 0.01 mg/g), hexosamine (31.37 ± 1.79 mg/g) and collagen (478.24 ± 1.12 mg/g) turnover were found to be significantly increased (p<0.05) in test topical herbal cream treated animals as compared to controls. All statistical analysis was performed using SPSS statistical version 20.0 software package and P-value was set as <0.05 for all analysis. Histopathological findings revealed that the cream confirmed that the epidermis layers with complete re-epithelialization and dermis show dense bundles of collagen fibers. In conclusion, all these investigations indicate significant wound healing potential of C. nutans topical herbal cream in Sprague Dawley excision wound models.